Neutron reflectivity studies of Aerosol-OT monolayers adsorbed at the oil/water, air/water and hydrophobic solid/water interfaces - Li, Z; Lu, JR; Fragneto, G; Thomas, R; Binks, B; Fletcher, P; Penfold, J (Elsevier, 1998)
The structures of monolayers of Aerosol-OT (sodium bis(2-ethylhexyl) sulfosuccinate) adsorbed at the oil/water, air/water and hydrophobic solid/water interfaces have been determined using neutron specular reflection in conjunction with isotopic substitution. The areas per molecule were found to be 78±2 Å and 80±5 Å at the critical micelle concentration (CMC=2.5 x 10-3 M), increasing to 132±5 Å at 8.0 x 10-6 M and 21 aut 3 ± 20 A2 at 2.5 x,10-6 M at the air/water and hydrophobic solid/water interfaces respectively. The thicknesses of the AOT layer at the air/water and solid/water interfaces were found to be 18±2 Å and 15±2 Å with no significant change with concentration. At the oil/water interface the thickness is much larger than the fully extended molecule and is 26±2 Å at an area per molecule of 68±2 Å2. This is probably caused by roughening of the oil/water interface by thermal fluctuations.